PELATIHAN APLIKASI KEUANGAN AKUNTANSIKU BAGI UMKM BINAAN WAHANA VISI INDONESIA JAKARTA - Saur Costanius Simamora; Safri Safri; Rita Intan Permatasari (Aptekmas Jurnal Pengabdian pada Masyarakat, 2021)
Micro, Small, and Medium Enterprises (MSMEs) are the most important businesses that have an important role in the economy in Indonesia. However, there are still many obstacles experienced by MSMEs assisted by Wahana Visi Indonesia in running their business, especially skills in business development and how to prepare excellent and correct financial reports. The situation analysis results show that more than 60% of MSMEs only record the amount owed by customers to the shop, record receivables from suppliers, record the amount of money in and money out and do not separate personal cash from their business activities. Community Service Activities (PKM) Faculty of Economics Universitas Dirgantara Marshal Suryadarma aims to provide material training and hands-on practice on how to make financial reports through the android-based financial application "AkuntansiKu" on a communication device (mobile phone). The result of this PKM activity is that only 56.6% of MSME entrepreneurs could correctly answer questions from the material presented before the training. However, after being given training and materials, the result was an increase to 78.2%. In addition, the majority of MSME entrepreneurs are already able to use the AkuntansiKu application.